Estudo da transesterificação do óleo de pinhão manso empregando catalisadores heterogêneos - Zanette, Andréia Fátima (2010)
The search for renewable sources of energy had increased intensely through the last years. By this way, biofuels are starting to play an important role as an alternative in opposition to fossil fuels. Biodiesel can be obtained by a transesterification reaction of oils with a short alcohol chain. In this regard, the species Jatropha curcas has been showing many advantages due its good quality of its extracted oil, yet it does not rival with food production. The use of heterogeneous catalysts presents itself as a promising alternative to the homogeneous catalysts, reducing biodiesel production costs, because the process of separation of the reaction results is simpler, there s not soap production, besides the possibility of re-using the catalyst. In this sense, the objective of this study was to valuate the efficiency of the following heterogeneous catalysts: resins, zeolites, clays, hydrotalcites, aluminas, and niobium oxide in the esters of fatty acids production, using methanol and Jatrophas curcas oil as substrates. For this finality, were made experimentation in a batch reactor in order to reach the catalysts screening in the following operational conditions: oil to methanol molar ratio of 1:9, 6 hours of reaction, 5 % (w/w) catalysts, at 6 °C to 120 °C. Results showed that an increasing in the temperature conduces an increment in the reaction s efficiency. Were selected two catalysts that presented the highest efficiency: clayl KSF and the resin Amberlyst 15, the both are commercial catalysts. A DCCR 23 complete experimental planning was made with this both catalysts to maximize the percentage of esters in the reaction. Independent variables and valuated levels in the planning were: temperature between 80 °C and 180 °C, oil to methanol molar ratio at 1:4 to 1:14, and catalyst percentage of 1 to 20% (w/w). Reaction conditions for a maximum efficiency in esters were: oil to methanol molar ratio of 1:12, 5 % (w/w) of catalyst, 160 °C and 6 hours of reaction, for both catalysts, obtaining a percentage of 70 % for clay and 60 % for the resin. It was also made a study of these catalysts re-utilization in five successive experiments in a batch reactor in the optimized reaction conditions for the both catalysts. It was observed an efficiency decrease in the number of the catalyst using cycles. In the fifth cycle the reaction efficiency was 37,5 % with the clay KSF and 25,2 % with the resin Amberlyst 15. As well, was searched the characterization of the catalysts about the area and the diameter of their pores by means of nitrogen isotherms and the application of the BET and BJH methods, which identified that the products present microporous and mesoporous. Yet, experiments were made to obtain the reaction kinetics in a batch reactor in the optimized conditions of the reaction. A simplified kinetic model was proposed, which described the reaction kinetics nicely.